Synthesis, characterization, and electrochemical uric acid sensing properties of Cu3N nanoparticles - Munusamy Settu; Gnanamoorthy Govindhan; Bavani Thirugnanam; Kumar Kalpana; Majed A. Alotaibi (Biosensors and Bioelectronics: X, 2024)
This article explores the development and applications of a Cu3N/GCE-based sensor using differential pulse voltammetry (DPV) for selective uric acid (UA) detection in clinical analysis. The sensor achieves a limit of detection (LOD) of 2.57 × 10−8 M and a quantification limit (QL) of 8.102 × 10−8 M, demonstrating its capability to precisely quantify minute UA concentrations. With rapid responsiveness and reusability over 25 days, it offers cost-effective monitoring of UA levels, even in complex sample matrices. Cu3N also exhibits high efficiency in degrading methylene blue (MB), achieving 87.7% degradation under optimized conditions, suggesting its potential as a photocatalyst for environmental remediation, particularly in dye degradation processes. Overall, Cu3N-based technologies show promise in sensitive UA detection for clinical diagnostics, environmental remediation, and industrial catalysis, highlighting its versatility and broad applicability across scientific and practical domains.